2021
DOI: 10.1007/s10528-021-10116-0
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Receptor Gene Polymorphisms and Risk of Knee Osteoarthritis: Possible Correlations with TNF-α, Macrophage Migration Inhibitory Factor, and 25-Hydroxycholecalciferol Status

Abstract: Osteoarthritis (OA) etiology and pathogenesis not yet fully understood. We studied the role of vitamin D receptor single-nucleotide polymorphisms (VDR-SNPs), vitamin D3, serum and synovial macrophage migration inhibitory factor (MIF), and tumor necrosis factor-α (TNF-α) in the development and progression of knee OA (KOA). This study included 205 Egyptian subjects (105 patients with KOA and 100 unrelated, healthy matched subjects selected as controls). The patient group was divided into three groups according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…In turn, Hassan et al (2022) [ 32 ] studied vitamin D receptor gene polymorphisms and the risk of osteoarthritis of the knee which may be correlated with TNF-α, a factor that inhibits macrophage migration (MIF), and 25-hydroxycholecalciferol concentration. The investigation included 205 participants which were assigned to the study (n = 105) and control group (n = 100).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In turn, Hassan et al (2022) [ 32 ] studied vitamin D receptor gene polymorphisms and the risk of osteoarthritis of the knee which may be correlated with TNF-α, a factor that inhibits macrophage migration (MIF), and 25-hydroxycholecalciferol concentration. The investigation included 205 participants which were assigned to the study (n = 105) and control group (n = 100).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the homozygous mutant CC genotype and C allele of TaqI may be considered as a risk factor in correlation with KOA development. As a result of the obtained results, it was concluded that VDR-SNPs, vitamin D3, TNF-α, and MIF have a potential function in the pathogenesis and progression of KOA with mechanistic associations [ 32 ]. Table 1 presents the most important research about the vitamin D metabolic pathway in total knee arthroplasty.…”
Section: Resultsmentioning
confidence: 99%
“…There is a complex interplay between vitamin D and the immune response to viral infections. Low vitamin D status is proposed to induce upregulation of the TNF-α and downstream of NF–ĸB1 signaling pathway, which regulates inflammatory reactions toward viral infection in macrophages [ 407 , 408 ]. Vitamin D was shown as a potent suppressor of IFN-γ-mediated macrophages response, preventing the release of inflammatory cytokines and chemokines [ 409 ].…”
Section: Factors Modulating Covid-19: a Mechanistic Understanding Via...mentioning
confidence: 99%